2021
DOI: 10.1080/13813455.2021.1876735
|View full text |Cite
|
Sign up to set email alerts
|

N-acetyl cysteine can blunt metabolic and cardiovascular effects via down-regulation of cardiotrophin-1 in rat model of fructose-induced metabolic syndrome

Abstract: BackgroundChronic fructose consumption is associated with development of obesity, insulin resistance (IR) and metabolic syndrome (MS). Cardiovascular diseases are linked to metabolic deregulation observed in MS. N-acetylcysteine (NAC) is a sulfur containing compound of Allium plants (such as garlic and onion) that increases intracellular reduced glutathione concentrations, which is an endogenous antioxidant. MethodsThis study investigated the ability of N-acetyl cysteine (NAC) to alleviate the metabolic disord… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 81 publications
(54 reference statements)
1
2
0
Order By: Relevance
“…Despite the lack of rigorous morphometric studies, collagen deposition was apparent only in the two groups of rats fed FHS in early life. The present finding is consistent with the findings of Abdelhaffez et al [ 69 ] who reported increased cardiac interstitial fibrosis after rats ingested 12 weeks of 20% fructose in their drinking water. Unfortunately, that study did not provide functional data.…”
Section: Discussionsupporting
confidence: 94%
“…Despite the lack of rigorous morphometric studies, collagen deposition was apparent only in the two groups of rats fed FHS in early life. The present finding is consistent with the findings of Abdelhaffez et al [ 69 ] who reported increased cardiac interstitial fibrosis after rats ingested 12 weeks of 20% fructose in their drinking water. Unfortunately, that study did not provide functional data.…”
Section: Discussionsupporting
confidence: 94%
“… 18 To the best of our knowledge, the majority of metabolomics studies on the effects of HFrD have focused on the analysis of urine and serum samples. 19 , 20 Thus, a systemic metabolomic analysis of high‐fructose‐influenced metabolic alterations is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, targeted metabolomics analysis of serum samples from women consuming a high‐fructose diet revealed that high fructose intake in healthy women might lead to metabolic alterations in acylcarnitine and lysophosphatidylcholine via interruption of mitochondrial β‐oxidation and lipid peroxidation 18 . To the best of our knowledge, the majority of metabolomics studies on the effects of HFrD have focused on the analysis of urine and serum samples 19,20 . Thus, a systemic metabolomic analysis of high‐fructose‐influenced metabolic alterations is still lacking.…”
Section: Introductionmentioning
confidence: 99%